Supercritical Carbon Dioxide Extraction Of Mango Seed Kernel Fat Blended With Palm Oil Mid-Fraction And Palm Stearin To Formulate Cocoa Butter Replacers - Akanda, Md. Jahurul Haque (2013)
Mango (Mangifera indica L.) is an important annual tropical fruit. Mango seed kernel (MSK) which is industrial by-product contains considerable amount of cocoa butter analogy fats. It is remarkable that no reports on the extraction of the mango seed kernel fat (MSKF) using supercritical carbon dioxide (SC-CO2) have been published. The aim of this work is to blend SC-CO2 extracted MSKF with palm oil mid-fraction (POMF) and palm stearin (PS) to formulate new cocoa butter replacers (CBRs). The physico-chemical properties, thermal properties, solid fat content (SFC) and morphology for the blends of MSKF: POMF and MSKF: PS conducted using different chromatographic and thermal techniques. Optimization of the SC-CO2 extraction parameters of MSKF from MSK were conducted using central composite design (CCD) of response surface methodology (RSM). The variables considered in the study are pressure (20-50 MPa), temperature (40-80 °C), and CO2 flow rate (1-4 ml/min). The optimized fat yield was predicted to be 11.29% at 44.2 MPa, 72.2 ºC and CO2 flow rate of 3.4 ml/min which was close to the fat yield (11.7%) of Soxhlet extraction. The blends containing 70 to 85% of MSKF had physico-chemical properties like fatty acid profiles, iodine value (IV), slip melting point (SMP), saponification value (SPV) and acid value (AV) close to that of commercial CB. Results showed that the major TG ranges in all blends were POP 11-38.8%, SOS 22.1-36.9%, and POS 15.4-16.2%, respectively.